1992
DOI: 10.1111/j.1753-6405.1992.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Future directions for mental health services in Australia

Abstract: The last decade has seen a marked increase in the attention given to mental health policy and services at both a state and national level. Mental health consumers, carers, service providers, and a number of professional bodies have contributed to the scrutiny of what had been a relatively neglected area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…From the outset of the National Mental Health Strategy in Australia in 1992, the need for linkages between the mental health sector and other government and non-government services was considered critical to the provision of effective community-based treatment and support (Australian Health Ministers, 1992; Whiteford, 1994). The first National Mental Health Policy and plan required: the mainstreaming of mental health services to bring them under the same administrative umbrella as other health services (Singh, 1992; Whiteford et al, 1993); the integration of hospital (inpatient) mental health services with community mental health services (Whiteford et al, 1993); and intersectoral linkages requiring access to housing and community services (mostly operated outside of health departments) for individuals with mental illness and psychiatric disability living in the community (Whiteford, 1992a; Whiteford, 1992b). Following deinstitutionalization, with most people with severe and persistent mental illness now cared for in the community, poor linkages between the health, housing, employment and income support sectors became evident (Behan et al, 1994; HREOC [Human Rights and Equal Opportunity Commission], 1993).…”
Section: Introductionmentioning
confidence: 99%
“…From the outset of the National Mental Health Strategy in Australia in 1992, the need for linkages between the mental health sector and other government and non-government services was considered critical to the provision of effective community-based treatment and support (Australian Health Ministers, 1992; Whiteford, 1994). The first National Mental Health Policy and plan required: the mainstreaming of mental health services to bring them under the same administrative umbrella as other health services (Singh, 1992; Whiteford et al, 1993); the integration of hospital (inpatient) mental health services with community mental health services (Whiteford et al, 1993); and intersectoral linkages requiring access to housing and community services (mostly operated outside of health departments) for individuals with mental illness and psychiatric disability living in the community (Whiteford, 1992a; Whiteford, 1992b). Following deinstitutionalization, with most people with severe and persistent mental illness now cared for in the community, poor linkages between the health, housing, employment and income support sectors became evident (Behan et al, 1994; HREOC [Human Rights and Equal Opportunity Commission], 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of mental health services into primary care, was designed to allow people with mental health problems to access quality mental health services close to their homes, families and daily activities 44. Using growth mixture models our study showed that treatment use was varied and treatment patterns were diverse for the women born 1973–1978 over time.…”
Section: Discussionmentioning
confidence: 93%
“…The inception of a National Mental Health Strategy (NMHS) and the first five-year National Mental Health Plan in 1992 marked an important turning point for mental health in Australia [ 8 , 9 ]. The subsequent 20 years of mental health reform saw the publication of further five-yearly Government Plans, each of which outlined priority areas for investment and reform.…”
Section: Introductionmentioning
confidence: 99%